Trust based obligations of the state and physician-researchers to patient-subjects - Miller, P B; Weijer, C (Journal of medical ethics, 2006)
When may a physician enroll a patient in clinical research? An adequate answer to this question requires clarification of trust-based obligations of the state and the physician-researcher respectively to the patient-subject. The state relies on the voluntarism of patient-subjects to advance the public interest in science. Accordingly, it is obligated to protect the agent-neutral interests of patient-subjects through promulgating standards that secure these interests. Component analysis is the only comprehensive and systematic specification of regulatory standards for benefit-harm evaluation by research ethics committees (RECs). Clinical equipoise, a standard in component analysis, ensures the treatment arms of a randomised control trial are consistent with competent medical care. It thus serves to protect agent-neutral welfare interests of the patient-subject. But REC review occurs prior to enrolment, highlighting the independent responsibility of the physician-researcher to protect the agent-relative welfare interests of the patient-subject. In a novel interpretation of the duty of care, we argue for a “clinical judgment principle” which requires the physician-researcher to exercise judgment in the interests of the patient-subject taking into account evidence on treatments and the patient-subject‘s circumstances.